Integration of sleep and emotion treatment: a randomized trial of transdiagnostic CBT for comorbid insomnia - Mahdieh Mohamadi Jam; Amirhossein Rasouli; Zahra Nejad-Ebrahim Soumee; Hoda Doosalivand; Omid Saed (BMC Psychiatry)
Abstract Background Insomnia frequently co-occurs with emotional disorders, yet integrated treatment approaches remain understudied. This study examined the efficacy of Transdiagnostic Cognitive Behavior Therapy (TCBT) for treating comorbid insomnia in patients with emotional disorders. Methods In this double-blind randomized controlled trial, 32 university students with comorbid insomnia and emotional disorders were randomly assigned to either TCBT (n = 16) or waitlist control (n = 16). The TCBT group received 20 one-hour sessions of treatment. Insomnia severity was assessed using the Insomnia Severity Index (ISI) at baseline, post-treatment, and three-month follow-up. Results Mixed-model ANOVA revealed significant main effects for time (F = 52.18, p < .001, Eta-Squared = 0.635) and group (F = 45.55, p < .001, Eta-Squared = 0.603), and a significant time × group interaction (F = 61.66, p < .001, Eta-Squared = 0.673). The TCBT group showed large effect sizes for insomnia reduction from pre- to post-treatment (Hedges’ g = 3.75) and pre-treatment to follow-up (g = 3.07), with benefits maintained at three months. The waitlist group showed no significant changes. Conclusions TCBT demonstrated robust efficacy in treating comorbid insomnia among university students with emotional disorders, with effects maintained at follow-up. These findings suggest TCBT as a promising integrated treatment approach for this population. Trial registration This randomized clinical trial comprised an intervention and a waitlist that was registered in the Iranian Registry of Clinical Trials (IRCT Id: IRCT20200112046097N1). (Registration Date: 26/07/2020).